A Confucian constitutional order : how China's ancient past can shape its political future - Jiang, Qing, 1953-; Bell, Daniel (Daniel A.), 1964-; Fan, Ruiping; Ryden, Edmund (Princeton, N.J. : Princeton University Press, 2012)
As China continues to transform itself, many assume that the nation will eventually move beyond communism and adopt a Western-style democracy. But could China develop a unique form of government based on its own distinct traditions? Jiang Qing--China's most original, provocative, and controversial Confucian political thinker--says yes. In this book, he sets out a vision for a Confucian constitutional order that offers a compelling alternative to both the status quo in China and to a Western-style liberal democracy. A Confucian Constitutional Order is the most detailed and systematic.
Introduction / Daniel A. Bell -- Part I.A Confucian constitutional order: the way of the humane authority: the way ahead for China's political future: the theoretical basis for Confucian constitutionalism and a tri-cameral parliament / Jiang Qing; The supervisory system of Confucian constitutionalism / Jiang Qing; A Confucian constitutionalist state: the constitutional role and Contemporary significance of republicanism under a symbolic monarch / Jiang Qing -- Part II. Comments: On the legitimacy of Confucian constitution / Joseph Chan; An old mandate for a new state: on Jiang Qing's political confucianism / Bai Tondong; Transcendent heaven? a critique of Jiang Qing's grounding of the right to rule / Li Chenyang; Is the way of the humane authority a good thing? an assessment of Confucian constitutionalism / Wang Shaoguang -- Part III. Responses to commentators: responses to critics / Jiang Qing.
Title from PDF title page (viewed on Oct. 24, 2012).
English translation of materials from a workshop on Confucian constitutionalism in May 2010 at the City University of Hong Kong.
Includes bibliographical references and index.
Master record variable field(s) change: 050
Keywords: Jiang, Qing, -- 1953- -- Political and social views; Jiang, Qing, -- 1953-; Jiang, Qing, -- 1953-; China -- Politics and government -- Philosophy; Confucianism and state -- China; POLITICAL SCIENCE -- Political Process -- General; POLITICAL SCIENCE -- Comparative Politics; Confucianism and state; Political and social views; Politics and government; China; Electronic books